Antibacterial susceptible pattern of ear, nose and throat in paediatric patient infections - Rajendran, Selvaraj; Cheekavolu, Chakrapani; Pathapati, Rama Mohan; Buchineni, Madhavulu (International Journal of Basic & Clinical Pharmacology, 2017)
Background: To study the bacterial pathogens of ear, nose and throat (ENT) to determine the frequency and sensitivity pattern of ENT infections in paediatric patients. Methods: The study was conducted during the period of June 2016 to May 2017 in Kerala Medical College Hospital. A total 225 samples were collected and evaluated for microbiological investigations. Antimicrobial susceptibility profile was determined by modified Kirby Bauer disc diffusion method. Results: Out of 225 samples, 140 (62.22%) were found positive growth and 85 (37.77%) of samples were found negative culture. The frequency of different organisms isolated was as follows: Pseudomonas 43 (30.71%), Staphylococcus aureus 32 (22.85%), Proteus spp. 18 (12.85%) Klebsiella spp. 17 (12.14%) etc., Antibiotic susceptibility pattern gram positive bacteria were vancomycin (100%) followed by amikacin (97.14%), and in gram negative bacteria; sulbactam/ cefoperazone (97.14%), piperacillin/tazobactam (95.23%) and meropenem (94.28%) were the most effective drugs. Conclusions: Pseudomonas aeruginosa, Staphylococcus aureus, Proteus spp. and Klebsiella spp. are the leading ENT pathogens in paediatric patients. Most of the isolates showed high resistance to cephalosporins. Showed high effectiveness to sulbactam/ cefoperazone, piperacillin/tazobactam.